1990
DOI: 10.1002/hlca.19900730703
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of the Conformation of Cyclosporin A in Chloroform

Abstract: New investigations of cyclosporin A in CDCl, have been performed to obtain additional and more accurate distance restraints than utilized in our previous studies of cyclosporin A. Build-up rates at 600 MHz using 6 different mixing times at low temperatures (252.5 K) were determined and transformed into distances using the two-spin approximation. With the new distance restraints in the MD simulations using the GROMOS package, we can unambiguously conclude the presence of a ,6II'-turn. The new structure resemble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
148
1
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(165 citation statements)
references
References 37 publications
14
148
1
2
Order By: Relevance
“…In addition, we propose that these co-existing conformations undergo rapid chemical exchange, which results in overlapping signals and hinders NMR structure determination. A few natural peptides were shown to assume multiple, stable, and distinct conformations; in these cases, NMR structure solution was possible albeit challenging (37)(38)(39). As the thermal instability of paeninodin prevented the recording of NMR spectra at higher temperatures, structure determination was deemed outside the scope of this study.…”
Section: Genome Mining Reveals a Novel Lasso Peptide Biosyntheticmentioning
confidence: 99%
“…In addition, we propose that these co-existing conformations undergo rapid chemical exchange, which results in overlapping signals and hinders NMR structure determination. A few natural peptides were shown to assume multiple, stable, and distinct conformations; in these cases, NMR structure solution was possible albeit challenging (37)(38)(39). As the thermal instability of paeninodin prevented the recording of NMR spectra at higher temperatures, structure determination was deemed outside the scope of this study.…”
Section: Genome Mining Reveals a Novel Lasso Peptide Biosyntheticmentioning
confidence: 99%
“…Walsh, unpubl.). It is likely that the mutant CyPs selectively bind the trans conformation of CsA, which exists in solution (Kessler et al, 1990;Altschuh et al, 1992) and has recently been shown to be the active species for PPIase inhibition (Kofron et al, 1992). In this view, the CyP active site serves solely as a scaffolding apparatus to present bound drug in an active conformation.…”
Section: Calcineurin Inhibition Studiesmentioning
confidence: 99%
“…The structure of CsA bound to CyP has recently been determined by NMR analysis Weber et al, 1991) and differs dramatically from CsA in solution (Kessler et al, 1990). Specifically, the 9,lO-amide bond is trans when bound and cis in solution.…”
mentioning
confidence: 99%
“…The performance of D G Q was compared with that of D G II, using cyclosporin A (CPA) (Lautz et al, 1987(Lautz et al, , 1989Kessler et al, 1990) as the target molecule for struc ture elucidation. The aim of this research was to present the principles underlying D G Q and to demonstrate that the approach can be used to generate improved struc tures.…”
Section: Resultsmentioning
confidence: 99%